First record of the nymph of Caenis cuniana Froehlich, 1969 (Caenidae: Ephemeroptera) and new distributional records of Caenidae from Colombia - Salinas-Jiménez , Luis Gonzalo; Lima, Lucas Ramos Costa; Rojas-Peña, Jose Ismael; Caro-Caro, Clara Ines (EntomoBrasilis, 2024)
In Colombia have been recorded eight species of the family Caenidae distributed in three states, at the moment do not exist species reported in the Meta state. In this paper, Caenis cuniana Froehlich, 1969 (Caenidae: Ephemeroptera) is registered for the first time from Colombia, in the same way, Brasilocaenis irmleri Puthz, 1975 and Caenis chamie Alba-Tercedor & Mosquera, 1999 expanded your geographical distribution in the Colombian Orinoquia region.